1991
DOI: 10.1182/blood.v78.11.2918.2918
|View full text |Cite
|
Sign up to set email alerts
|

Hypercytokinemia in familial hemophagocytic lymphohistiocytosis

Abstract: Familial hemophagocytic lymphohistiocytosis (FHL) is a frequently missed and almost uniformly fatal childhood disorder. It is characterized by fever, hepatosplenomegaly, cytopenia, coagulopathy, and hypertriglyceridemia. The pathogenesis of FHL is not known but the above clinical and laboratory findings are compatible with reported in vitro and in vivo effects of several inflammatory cytokines. We measured circulating interferon-gamma (IFN-gamma), tumor necrosis factor/cachectin (TNF), and interleukin-6 (IL-6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(146 citation statements)
references
References 23 publications
7
135
0
3
Order By: Relevance
“…This is partially consistent with previous reports (Osugi et al , 1997; Murohashi et al , 2006). Some reports also found that TNF‐α was moderately elevated in most HPS cases, which is consistent with the factor that macrophages are over‐activated in HPS (Henter et al , 1991b; Akashi et al , 1994), but the level was not as high as IFN‐γ and IL‐10. Most cases had reported TNF levels <20 IU/ml (320 pg/ml) (Henter et al , 1991b).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This is partially consistent with previous reports (Osugi et al , 1997; Murohashi et al , 2006). Some reports also found that TNF‐α was moderately elevated in most HPS cases, which is consistent with the factor that macrophages are over‐activated in HPS (Henter et al , 1991b; Akashi et al , 1994), but the level was not as high as IFN‐γ and IL‐10. Most cases had reported TNF levels <20 IU/ml (320 pg/ml) (Henter et al , 1991b).…”
Section: Discussionsupporting
confidence: 70%
“…Numerous well‐differentiated macrophages phagocytosing haematopoietic cells can usually be found in the bone marrow, liver, spleen or lymph nodes (Henter et al , 1991a, 1997, 2007). The clinical presentation of HPS is caused by a hyperinflammatory syndrome resulting from hypercytokinemia of various pro‐inflammatory mediators, such as interferon‐γ (IFN‐γ), tumour necrosis factor‐α (TNF‐α), interleukin (IL)‐6, IL‐8, IL‐12, IL‐18, macrophage–colony‐stimulating factor (M‐CSF), and a number of haematopoietic growth factors released by stimulated lymphocytes and macrophages (Henter et al , 1991b; Akashi et al , 1994; Osugi et al , 1997; Takada et al , 2001; Mazodier et al , 2005).…”
mentioning
confidence: 99%
“…In addition, many of the patients develop progressive cerebromeningeal symptoms during the course of the disease (Henter & Elinder, 1992; Haddad et al , 1997; Henter & Nennesmo, 1997). Typical for the pathogenesis of HLH is a defect in apoptosis triggering and in natural killer (NK) and cytotoxic T lymphocyte (CTL) cellular cytotoxicity (Arico et al , 1988; Fadeel et al , 1999; Schneider et al , 2002) associated with a prominent overproduction of several inflammatory cytokines (Henter et al , 1991a; Osugi et al , 1997). Without treatment including hematopoietic stem cell transplantation (SCT), FHL is inevitably fatal (Henter et al , 2002; Ouachee‐Chardin et al , 2006).…”
mentioning
confidence: 99%
“…Fever and cytopenias are prominent in FHL and may be induced by several cytokines, such as TNF, IL‐6 and IFN‐γ. TNF also has a procoagulant activity, which may account for the hypofibrinogenaemia [17]. The hypertriglyceridaemia is associated with reduced lipoprotein lipase, due to the presence of TNF [18].…”
Section: Pathophysiologymentioning
confidence: 99%